(untitled) (Research, Society and Development, 2021)
This article discusses the choice of school managers and the Dinheiro Direto na Escola Program - PDDE as mechanisms for participation in the school. The objective is to reflect on the role of the Direct Money Program at School and the choice of the school manager as mechanisms for strengthening democratic management, understanding the barriers and advances of these mechanisms in the society of capital. The problem that this research proposes to answer is: How can the choice of school managers and the PDDE contribute to the strengthening of democratic management in the educational system? The research methodology is qualitative and the analyzes were based on a bibliographic study. The results show the importance of democratic management being effectively permeated by this principle, serving as a foundation for strengthening spaces for participation, the decentralization of power and the exercise of citizenship within the municipality, as well as the forms of choice of school managers and the PDDE and other instances of involvement of the school community is an important step towards the democratization of decision-making processes and sharing of power. We can conclude that the democratization of education management requires the participation of different sections and different segments of the community.